Transformative Pedagogy of Multiliteracies and the Challenges of Cultural Constraint in Indonesia - Yuniar Dwi Ansari Siregar; Rizki Ramadhan (Journal of English Language Teaching and Islamic Integration, 2018)
This paper intends to see the literacy pedagogy in Indonesia from  the  point  of  view  of  transformative  pedagogy  of  multiliteracies (Cope  and  Kalantzis,  2009).  It  can  be  argued  that  the  educational change  in  Indonesia  is  moving  away  from  the  overt  instruction (conceptualizing)  orientation  of  literacy  pedagogy  to  the  transformed practice  (applying)  orientation  of  literacy  pedagogy.  Beside  the convincing  argument  that  this  change  is  needed,  there  are  several challenges in applying this practice in the classroom and one of it is the cultural constraint. This paper will try to describe Indonesian culture of learning as the basic argument of cultural constraint challenges and as an  attempt  to  see  the  literacy  movement  in  Indonesia  from  the sociocultural  perspective  of educational  change.  This  description  will then  help  framing  the  implications  both  for  teachers  as  the  agent  of change and for government as on how to manage the change. Data and support written in this article are from secondary sources as this article intends to be a literature review. Suggestions coming from the literature discussed  that  a  „collaborative  work  culture‟  (Fullan  &  Hargreaves, 1992) is the solution of the challenge in implementing a transformative pedagogy of multiliteracies in Indonesian context.